2010
DOI: 10.1111/j.1365-246x.2010.04574.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of coda wave attenuation in the Alborz region and central Iran

Abstract: S U M M A R YMore than 340 earthquakes recorded by the Institute of Geophysics, University of Tehran (IGUT) short period stations from 1996 to 2004 were analysed to estimate the S-coda attenuation in the Alborz region, the northern part of the Alpine-Himalayan orogen in western Asia, and in central Iran, which is the foreland of this orogen. The coda quality factor, Q c , was estimated using the single backscattering model in frequency bands of 1-25 Hz. In this research, lateral and depth variation of Q c in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 62 publications
2
32
2
Order By: Relevance
“…To invert phase and group velocity dispersions, we used the average Q S structural models to avoid anelastic dispersion effect. The average values of Q S are taken from the literature as ∼25 and ∼55 for crust and upper mantle (Cong and Mitchell, 1998;Motazedian, 2006;Rahimi and Hamzehloo, 2008;Ma'hood et al, 2009;Rahimi et al, 2009Rahimi et al, , 2010.…”
Section: Constructing the Starting Modelmentioning
confidence: 99%
“…To invert phase and group velocity dispersions, we used the average Q S structural models to avoid anelastic dispersion effect. The average values of Q S are taken from the literature as ∼25 and ∼55 for crust and upper mantle (Cong and Mitchell, 1998;Motazedian, 2006;Rahimi and Hamzehloo, 2008;Ma'hood et al, 2009;Rahimi et al, 2009Rahimi et al, , 2010.…”
Section: Constructing the Starting Modelmentioning
confidence: 99%
“…Attenuation of the Alborz region has been studied by several investigators using different dataset and methods (e.g., Motazedian, 2006;Rahimi et al, 2010;Motaghi and Ghods, 2012;Naghavi et al, 2012). In this study, we estimated attenuation of the coda wave by using the SBS (Aki and Chouet, 1975) and single isotropic-scattering (SIS) models (Sato, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Jin and Aki, 1986;Havskov et al, 1989;Ibañez et al, 1990;Singh and Hermann, 1983;Hellweg et al, 1995;Mukhopadhyay and Tyagi, 2007;Mukhopadhyay et al, 2008;Rahimi et al, 2010;Singh et al, 2011a) have shown that Q 0 is normally high in stable regions and low in active tectonic regions while its frequency dependence parameter n has an inverse behavior. In Fig.…”
Section: Comparison Of Q C With Global Observationsmentioning
confidence: 91%